Potential for dietary exposure to β-N-methylamino-L-alanine and microcystin from a freshwater system. (August 2018) - Scott, Laura L.; Downing, Simoné; Downing, Tim
Abstract: The suggested link between β- N -methylamino-L-alanine (BMAA) and the onset of neurodegenerative diseases and the detection of this cyanotoxin in aquatic organisms has prompted research into the potential human exposure risk associated with sourcing food items from eutrophied water bodies worldwide. The Hartbeespoort Dam reservoir in the North West province of South Africa has persistent cyanobacterial blooms and is used extensively by anglers, many of whom consume their catch. The commercial sale of fish species harvested from this reservoir as part of a recent biomanipulative remediation strategy may pose an additional hazard. BMAA and Microcystins (MC) were detected in fish sourced from this reservoir. BMAA levels of up to 1630 ng g −1 dry weight and MC concentrations of up to 29.44 ng g −1 dry weight were detected in fish sourced during an extensive bloom episode, with a clear correlation between the total amount of BMAA detected in the fish muscle tissue and their relative position in the Hartbeespoort Dam reservoir food web. Interestingly, fish sourced from this reservoir in winter when dense cyanobacterial blooms were lacking contained BMAA levels of up to 3055 ng g −1 dry weight. We also comment on the observed seasonal variations of BMAA levels in phytoplankton and fish sourced from this water body as well as the potential exposure risks associated with harvesting food items from this reservoir. Highlights: BMAA and microcystins accumulate in fish sold for human consumption. Cyanobacterial bloom density, or presence, does not correlate with cyanotoxins in fish. BMAA and microcystin amounts are inversely related in natural samples. BMAA and microcystin concentrations are a function of biologically available nitrogen.